ERYTHROCYTE SEDEMENTATION RATE:A USEFUL TOOL IN DIAGNOSTIC APPROACH - Muhammad Usman (Baqai Journal of Health Sciences)
Erythrocytes Sedimentation Rate (ESR) is one of the most common lab tests requested by physicians across the globe. Although it doesn’t enjoy the status of being called a diagnostic test,even then it is in continuous use as a good indicator in conditions like infections and inflammations; for screening and prognosis of certain diseases and also for monitoring the course of an existing disease.It is a good indicator to estimate the quantitative change in plasma that may occur in a lot of clinical conditions ranging from simple to much serious disorders such as inflammation, infection, pregnancy, obesity and even malignancies. In certain hematological conditions such as polycythaemia, sickle cell anaemia, leukemia, hypoproteinaemia as well as few other conditions like hyper viscosity, congestive heart failure etc. Physicians does rely on ESR as an indicator to some extent. Current review is done to check its clinical impo